Towards a Materialist Concept of the History of Science: Muslim Science Fuses East and West - Tomczak, Matthias (The international journal of religion and spirituality in society, 2016)
On two occasions in history did the birth of a new religion have a profound effect on the development of science. The birth of Christianity coincided with the decline of European science; the birth of Islam brought its revival. It is argued that this difference is the result of different economic and political conditions. The Syriac Christian community maintained learned institutions where scientific knowledge was preserved but was isolated from Europe, where a dogmatic church persecuted science as pagan magic and laid the ground for Europe’s "Dark Ages." Islam turned religion into a religion of conquest that embraced science as an instrument of empire building. Its ruling class supported the collection of knowledge from all parts of its empires, fusing Greek and Indian science into a new Muslim science in the process.